Role of Acacia species - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Role of Acacia species in the rural economy of dry Africa and the Near East by G Wickens 1995 ISBN 92 5 1036519